Additions and Corrections - SUPPLEMENT (Biomedical papers, 2003)
This additional contribution becomes an integral part of the Biomedical Papers, Volume 147,SUPPLEMENT 1, October 2003, dedicated to the XXIX Congress of the Czech and SlovakGastroenterological and Hepatological Societies, held October 2-4, 2003 in Olomouc, Czech Republic.Editors express their apology to the authors for non-inclusion of the above contribution to the collection volume of the Biomed. Papers, which was caused by technical problems.
Keywords: Additions and Corrections